Ameliorative effect of Albizia chinensis synthesized ZnO-NPs on Mycoplasma pneumoniae infected pneumonia mice model. (April 2020) - Yu, Liping; Lu, Man; Zhang, Wenzhi; Alarfaj, Abdullah A.; Hirad, Abdurahman H.; Zhang, Haixian
Abstract: Background: Mycoplasma pneumoniae (MP) is a common cause of community-acquired pneumonia (CAP) among the children and adults that results upper and lower respiratory tract infections. Objective: This study was aimed to inspect the ameliorative action of A. chinensis synthesized ZnONPs against M. pneumoniae infected pneumonia mice model. Materials and methods: ZnO NPs was synthesized from Albizia chinensis bark extract and characterized by UV–Vis spectroscopy, Fourier Transform Infrared (FTIR), Transmission Electron Microscopy (TEM), energy dispersive X-ray (EDX) and atomic force microscope (AFM) analyses. The antibacterial effectual of synthesized ZnONPs were examined against clinical pathogens. The pneumonia was induced to BALB/c mice via injecting the M. pneumoniae and treated with synthesized ZnONPs, followed by the total protein content, total cell counts and inflammatory mediators level was assessed in the BALF of experimental animals. The Histopathological investigation was done in the lung tissues of test animals. Results: The outcomes of this work revealed that the formulated ZnONPs was quasi-spherical, radial and cylindrical; the size was identified as 116.5 ± 27.45 nm in diameter. The in vitro antimicrobial potential of formulated ZnO-NPs displayed noticeable inhibitory capacity against the tested fungal and bacterial strains. The administration of synthesized ZnO-NPs in MP infected mice model has significantly reduced the levels of total protein, inflammatory cells, inflammatory cytokines such as IL-1, IL-6, IL-8, tumour necrosis factor-alpha (TNF-a) and transforming growth factor (TGF). Besides, the histopathological examination of MP infected mice lung tissue showed the cellular arrangements were effectively retained after administration of synthesized ZnO-NPs. Conclusion: In conclusion, synthesized ZnO-NPs alleviate pneumonia progression via reducing the level of inflammatory cytokines and inflammatory cells in MP infected mice model. Graphical abstract: Image 1 Highlights: Pneumonia is the most persistent infectious disease, which causes enormous socio-economic burden. ZnONPs is a multifunctional nano-material with chemical and physical stability, and strong bactericidal activity. The synthesized ZnONPs from A. chinensis has effectively ameliorated the MP infection triggered lung injury in pneumonia.